Improvement of Fab expression by screening combinatorial synonymous signal sequence libraries - Kulmala A; Huovinen T; Lamminmäki U (BMC, 2022)
Background Antibody fragments can be expressed in Escherichia coli, where they are commonly directed to the periplasm via Sec pathway to enable disulphide bridge formations and correct folding. In order to transport antibody fragments to the periplasmic space via Sec pathway, they are equipped with N-terminal signal sequence. Periplasmic expression has many benefits but it's also subjected to many hurdles like inefficient translocation across the inner membrane and insufficient capacity of the translocation system. One solution to overcome these hurdles is a modulation of codon usage of signal sequence which has proved to be an efficient way of tuning the translocation process. Modulation of codon usage of signal sequences has been successfully employed also in improving the expression levels of antibody fragments, but unfortunately the effect of codon usage on the expression has not been thoroughly analyzed. Results In the present study we established three synonymous PelB signal sequence libraries by modulating codon usage of light chain and heavy chain PelB signal sequences of a Fab fragment. Each region (n-region, hydrophobic region and c-region) of the PelB signal sequence in the both chains of the Fab fragment in a bicistronic expression vector was mutated separately. We then screened for clones with improved expression profile. The best source for improved clones was the n-region library but in general, improved clones were obtained from all of the three libraries. After screening, we analyzed the effects of codon usage and mRNA secondary structures of chosen clones on the expression levels of the Fab fragment. When it comes to codon usage based factors, it was discovered that especially codon usage of fifth leucine position of the light chain PelB affects the expression levels of Fab fragment. In addition, we observed that mRNA secondary structures in the translation initiation regions of the light and heavy chain have an effect on expression levels as well. Conclusions In conclusion, the established synonymous signal sequence libraries are good sources for discovering Fab fragments with improved expression profile and obtaining new codon usage related information.